A Modified Pugh Matrix Method for Continuous Performance Evaluation of Employees. (June 2022) - Sreejith, S. S.; Mathirajan, M.
Although researchers recommend the continuous performance evaluation of employees (CPEE), literature is scant about a procedural framework for CPEE. This article aims to develop a simple and robust method for CPEE using the modified Pugh matrix method (MPMM). The criteria for CPEE are compared pairwise using the analytical hierarchy process (AHP), followed by a comparison of employees using MPMM to determine and rank the employees based on their performance. The proposed method is successfully validated in an organisation, and the working mechanism of MPMM is demonstrated. Implications of the proposed method for CPEE and the scope for future work are also discussed.